Carlos Alberto Seguin: San Fernando School of Medicine’s teacher paradigm, 100 years from his birth - Perales, Alberto (2008)
Celebrating Carlos Alberto Seguin’s first birth centenary (1907-2007) the author describes three facets of his exemplary life: his formative years, his presence in San Fernando School of Medicine during the difficult 60’s and his dignified attitude facing death. The advanced Seguin’s ideas upon medical education reform, joining the psyche and physical parts of human beings as an integral whole made him postulate to diagnose and treat not only ‘the illness’ but the whole person. Moreover, his methodological proposal of ‘formative groups’ in order to give the students the opportunity to elaborate their emotional reactions while interacting patients, were not well understood and caused conflicts that he preferred to avoid for the institution’s sake. He sadly understood that students of that time were not willing to make the necessary efforts to reach their best academic goal. Finally, his dignified attitude in front of death is described in a poem he wrote just before dying. Seguin died on Saturday August 26, 1995. He should be remembered as a sanmarquino teaching paradigm.